Repression And Mobilization - Mueller, Carol McClurg; Johnston, Hank, 1947-; Davenport, Christian, 1965- (Book collections on Project MUSE., 2005)
With case studies that range from Germany to the Philippines, the United States to Japan, Guatemala to China, these essays synthesize what we know about repression and mobilization and provide thoughtful insight for the future.